Poorly Differentiated Breast Carcinoma is Associated with Increased Expression of the Human Polycomb Group EZH2 Gene - Raaphorst, Frank M. (Neoplasia Press Inc., 2003)
Polycomb group (PcG) genes contribute to the maintenance of cell identity, cell cycle regulation, and oncogenesis. We describe the expression of five PcG genes (BMI-1, RING1, HPC1, HPC2, and EZH2) in normal breast tissues, invasive breast carcinomas, and their precursors. Members of the HPC-HPH/PRC1 PcG complex, including BMI-1, RING1, HPC1, and HPC2, were detected in normal resting and cycling breast cells. The EED-EZH/PRC2 PcG complex protein EZH2 was only found in rare cycling cells, whereas normal resting breast cells were negative for EZH2. PcG gene expression patterns in ductal hyperplasia (DH), well-differentiated ductal carcinoma in situ (DCIS), and well-differentiated invasive carcinomas closely resembled the pattern in healthy cells. However, poorly differentiated DCIS and invasive carcinomas frequently expressed EZH2 in combination with HPC-HPH/PRC1 proteins. Most BMI-1/EZH2 double-positive cells in poorly differentiated DCIS were resting. Poorly differentiated invasive carcinoma displayed an enhanced rate of cell division within BMI-1/EZH2 double-positive cells. We propose that the enhanced expression of EZH2 in BMI-1(+) cells contributes to the loss of cell identity in poorly differentiated breast carcinomas, and that increased EZH2 expression precedes high frequencies of proliferation. These observations suggest that deregulated expression of EZH2 is associated with loss of differentiation and development of poorly differentiated breast cancer in humans.